2020
DOI: 10.3390/medicina56040182
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Cardiovascular Events in Hypertensive Patients with High Cardiovascular Risk

Abstract: Background and objectives: A long-term therapeutic strategy in hypertensive patients equally depends on measured arterial blood pressure values and total determined cardiovascular risk. The aim of the adequate hypertensive patient treatment is both the reduction in arterial blood pressure and the reduction of all preexisting modifiable risk factors, prevention of target organs damage, and adverse cardiovascular events. The aim of this study was to determine independent predictors of cardiovascular events in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Categorical variables were compared using a Chi-squared or Fischer's exact test, depending on group size. The statistical package SPSS (version 21.0, IBM Corp, 2012; Armonk, NY, USA) was used for all statistical data processing [12]. A two-sided p < 0.05 was considered to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Categorical variables were compared using a Chi-squared or Fischer's exact test, depending on group size. The statistical package SPSS (version 21.0, IBM Corp, 2012; Armonk, NY, USA) was used for all statistical data processing [12]. A two-sided p < 0.05 was considered to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the proportion of subjects with diabetes and hypertension did rise with the severity of plaque. This may caused by disorders of glucose and lipid metabolism in most diabetes or hypertension patients, and the incidence of carotid plaques is increased [29][30][31][32][33]. Thus in further analysis, we compared subjects with diabetes, hypertension and those without these two diseases respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with missing data were excluded from the study at its very beginning when the data were collected. The statistical package SPSS (version 21.0, Armonk, NY, USA: IBM Corp, 2012) was used for all of the statistical data processing [15]. A two-sided p < 0.05 was considered to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%